(3GdJShjb GdeYGUQs - (3KGHJ YHO GdQMef(B, (3GOQjSs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2005)
(3GdJShjb aj Xd YGde eJZjQ(B- (3GdOhQ GdESJQGJjLj ddJShjb aj GdefXeI GdeYGUQI(B- (3JMdjd GdHjFI GdJShjbjI(B- (3fXe GdeYdheGJ GdJShjbjI hHMhK GdJShjb(B- (3JbSje GdShb Gdi bWGYGJ(B- (3GSJQGJjLjI GdefJLGJ(B- (3GSJQGJjLjI GdJSYjQ(B- (3GSJQGJjLjI GdJhRjY(B- (3GdJShjb GdeHGTQ(B- (3GdJShjb GdEdcJQhfj(B- (3GdeSDhdjI GdELJeGYjI hCNdGbjGJ GdJShjb(B.s
Keywords: (3GdJShjbs